GIG ECONOMY, ALTERNATIVE FORMS OF WORK IN RURAL AREAS, IN THE CURRENT ECONOMIC AND SOCIAL CONTEXT - Sarina ROSENBERG; Dragos CRISTEA; Mihaela NECULIȚĂ; Ira-Adeline SIMIONOV; Ștefan-Mihai PETREA; Alina MOGODAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In the current economic and social context, dominated by the influences of the rapid development of technology and communications, the labour market is undergoing structural changes, job demand and supply are reshaping, labour arrangements are resizing in form and volume. Another factor that significantly affects the structure and dynamics of the labour market is the current health crisis. The negative impact on the various economic sectors affected by the crisis implicitly entails changes in the balance between job demand and supply, as well as the reassessment and decision to choose effective work arrangements. GIG economy, representing all atypical forms of work, presents an increasingly complicated and difficult to predict dynamics, as a result of the economic and social impact of current factors of influence. The purpose of the article is to analyze and predict the dynamics of different forms of work in the Romanian rural areas, starting with the forms of full time, permanent contracts to contingent forms of work. The analysis method used in this paper is the quantitative one. From the analysis performed, it can be deduced observations and results that define the general framework of all forms of work in Romanian rural environment and the dynamic tendencies of the different forms of work commitment during the analyzed period. Full time contracts, regardless of how they are registered, as a determined or indefinite period, have the largest share of the total number registered at national level in rural areas. On the other side, part-time contracts register different dynamic trends, in the sense that the permanent ones have an ascending trend, and the contingent forms register a sudden collapse in the period 2017-2018, by approximately 400% compared to previous years. Part time permanent jobs increase with 67.43% in 2020 compared to 2010.